KEABSAHAN RAPAT UMUM PEMEGANG SAHAM (RUPS) DALAM PERALIHAN SAHAM YANG BERASAL DARI OBJEK PPJB YANG BELUM LUNAS: STUDI PUTUSAN NOMOR 29/PDT.SUS-GLL/2022/PN NIAGA.JKT.PST - Ayu Wulandari Damanik, Wiwin; Sunarmi, Sunarmi; Robert, Robert (Penerbit Lafadz Jaya, 2025)
The General Meeting of Shareholders (GMS) is a company organ that holds the highest power in the company and holds all authorities that are not delegated by the directors and commissioners. In the transfer of shares in the Company, a General Meeting of Shareholders must first be held as in accordance with the provisions of Article 56 of Law Number 40 of 2007 concerning Limited Liability Companies. The objectives of this thesis include analyzing the validity of the GMS in a Limited Liability Company regarding the Transfer of Shares from PPJB that has not been Paid in Full, analyzing the legal consequences of the Sale and Purchase Agreement (PPJB) for PPJB Objects that have not been paid in full in a bankrupt company, and analyzing the judge's considerations in the District Court decision No. 29 / Pdt.SUS-GLL / 2022 / PN.Niaga.Jkt.Pst. The type of research used is Normative Legal Research which will refer to laws and regulations. Normative legal research in this study was carried out using a statute approach and a case approach. The data sources used are Primary Legal Materials (written rules enforced by the state) Secondary Legal Materials (materials in the form of legal reviews) Tertiary Legal Materials (materials that support legal materials, both primary and secondary). Data collection techniques are through legal material literature studies (rechtsmaterialen) and field research through interviews. The results of this thesis research can be concluded firstly the validity of a GMS in a Company can be seen in Law No. 40 of 2007 concerning Limited Liability Companies based on its material and formal elements. Secondly the legal consequences of the Sale and Purchase Agreement (PPJB) for the PPJB Object that has not been paid off in a bankrupt company are null and void, because the payment obligation has not been fulfilled. The three considerations of the judge in the decision were to sentence and order the Defendant (Curator) to remove the Immovable Assets, namely two apartment units owned by the plaintiff, from the Bankruptcy Asset List, as well as to remove them from all documents related to the bankrupt Assets (budel) and to declare that the Curator had committed an Unlawful Act (PMH).